Sulphate Resistance of Geopolymer Concrete Based on High Calcium Fly Ash - Yuyun Tajunnisa; Nur Achmad Husin; Indra Komara; Mochammad Ahdian Wildan Nafi; Mitsuhiro Shigeishi (IPTEK The Journal of Engineering, 2023)
The inclusion of fly ash class C, which is widely available locally, can influence the progress of strength and durability qualities of geopolymer concrete when exposed to significant environmental conditions. Alternative geopolymer combinations appropriate for curing at ambient temperatures were employed to investigate the impacts of fly ash class C based geopolymer concrete. To react with fly ash class C, a combination of sodium hydroxide and sodium silicate alkaline activator was used. Fly ash class C was added as 20% of the total binder without using ordinary Portland cement. The durability of fly ash class C based geopolymer concrete in sulphate environments was tested. The changes in weight, length and compressive strength due to exposure in magnesium sulphate solution for different periods of time were determined. The test results demonstrate that fly ash class C based geopolymer concrete cured at normal temperatures has good resistance to sulphate attack. In general, inclusion of fly ash class C in geopolymer concrete improved strength and performed satisfactorily in sulphate environments when cured in ambient temperature.